SYNTHESIS AND EVALUATION OF ANTIOXIDANT AND ANTIINFLAMMATORY ACTIVITIES OF 2-(4’-DIMETHYLAMINO BENZYLIDENE)-6-BENZYLIDENE CYCLOHEXANONE - Sardjiman .; Ni Nyoman Yuliarti; Sasmito .; Agung Endro Nugroho (Indonesian Journal of Pharmacy, 2013)
The study was designed to investigate whether 2-(4’-dimethylamino benzylidene)-6-benzylidene cyclohexanone (named code “B”) can be synthesized by reaction of Claissen–Schmidt condensation with 4'-dimethylamino benzal-dehyde, benzaldehyde, and cyclohexanone as starting materials and to evaluate its antioxidant and anti-inflammatory activities. The study showed that compound B at the concentration of 5, 10, 20, 40, and 80ppm did not exhibit antioxidant activity. In order to access the antiinflammatory activity, this compound was administered orally an hour before intra-plantar injection of carraagenan 1% on rat paw. Anti-inflammatory effect was evaluated by measuring the volume of edema every hour for 5h. Statistical analysis was performed by one way anova at 95% confidence level and followed by LSD test. “B” was potential as an anti-inflammatory agent at the dose of 132.40mg/200g BW by decreasing the volume of paw edema.Key words: synthesis; 2-(4’-dimethylaminobenzylidene)-6-benzylidene cyclohexanone; antioxidant; anti-inflammatory